THE DEVELOPMENT OF FLIP-BASED CHEMISTRY ILLUSTRATION - Sari, Sri Adelila; Hasibuan, Hanisah (PROSIDING SEMINAR KIMIA, 2023)
One of the causes of low student learning outcomes is the lack of student interest in chemistry learning. This is also due to students' disinterest in reading chemistry textbooks provided by the school. This study was aimed to obtain feasibility, effectiveness, teacher and student responses to flip-based chemistry illustration on equilibrium of acid and base ions. The research method used was research & development (R&D) with a 4D model which consists of 4 stages, namely define, design, develop, and disseminate. This research was conducted at the XI-F class SMA Negeri 2 Percut Sei Tuan. The results showed that flip-based chemical illustration books met the good criteria. Evaluation of the feasibility of flip-based chemical illustration books by material experts with an average percentage of 78 percent in the feasible category and 75 percent from media experts in the feasible category. Meanwhile, based on the N-Gain score of 0.62 in the moderate category, flip-based chemistry illustration books was found to be effective in improving student learning outcomes. Overall, the response of the chemistry teacher and students gave a positive response to flip-based chemistry illustration books with a percentage of 100 85, respectively. This study concluded that flip-based chemistry illustration book on equlibirium of acid and base ions was feasible to apply in chemistry learning. Keywords: Development, chemistry illustration book, and flip